2015
DOI: 10.1002/anie.201508646
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Origin of Tramadol in the Environment

Abstract: The presence of tramadol in roots of Sarcocephalus latifolius trees in Northern Cameroon was recently attributed to point contamination with the synthetic compound. The synthetic origin of tramadol in the environment has now been unambiguously confirmed. Tramadol samples isolated from tramadol pills bought at a street market in downtown Maroua and highly contaminated soil at Houdouvou were analyzed by high-precision (14)C measurements by accelerator mass spectrometry ((14)C AMS): Tramadol from the pills did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…10,11 Tramadol addiction is recognized to cause adverse and in some cases lethal health effects. 12 Cannabis, which is derived from the plant Cannabis sativa, has been tangled with human culture from the dawn of history. 13 Cannabis is broadly supposed as a safe recreational drug and its use is increasing among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Tramadol addiction is recognized to cause adverse and in some cases lethal health effects. 12 Cannabis, which is derived from the plant Cannabis sativa, has been tangled with human culture from the dawn of history. 13 Cannabis is broadly supposed as a safe recreational drug and its use is increasing among adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, the group of M. Spiteller from the University of Dortmund (Germany) suggested that tramadol detected in the roots of N. latifolia was due to anthropogenic contamination, likely to be derived from the misuse of tramadol in ethnoveterinary practices. 13 These data validate their proposal that tramadol is widely abused in ethnoveterinary use, but do not invalidate the claim that the tramadol isolated from N. latifolia is of natural origin. The situation is confused, as the same group have detected trace amounts of tramadol, along with three mammalian metabolites (O-desmethyltramadol, N-desmethyltramadol and 4-hydroxycyclohexyltramadol), in the roots of ve plant species and in soil collected over a wide sampling area.…”
Section: The Tramadol Controversymentioning
confidence: 58%
“…The situation is confused, as the same group have detected trace amounts of tramadol, along with three mammalian metabolites (O-desmethyltramadol, N-desmethyltramadol and 4-hydroxycyclohexyltramadol), in the roots of ve plant species and in soil collected over a wide sampling area. 13 Although only one sample of N. latifolia root contained sufficient tramadol to carry out this analysis, it gave a value consistent with a modern atmosphere and inconsistent with fossil origin. Independent analysis by the Dortmund lab of the sample used for the initial isolation conrmed a high tramadol content of 0.4% w/w in this sample.…”
Section: The Tramadol Controversymentioning
confidence: 95%
See 2 more Smart Citations